Bevacizumab in the treatment of epithelial ovarian carcinoma. (June 2014) - Davidson, Brittany A; Secord, Angeles Alvarez
In recent years, inhibitors of angiogenesis have become a focus of clinical trials aimed at expanding treatment options for women afflicted with epithelial ovarian cancer (EOC). Bevacizumab, a VEGF inhibitor, has been well studied in multiple solid tumors, suggesting progression-free and overall survival benefits. In EOC, bevacizumab has been the subject of many trials with results indicating a progression-free survival benefit in a variety of settings. The addition of bevacizumab to the EOC armamentarium, however, is not without risk. This article provides a rationale for targeting angiogenesis and discusses pivotal trials evaluating the utility of bevacizumab in EOC. Current research is evaluating optimal dosing duration, benefit of bevacizumab beyond progression, biomarkers to direct anti-angiogenic therapy and patient reported outcomes.